Los criterios ADA-97, la prevalencia de diabetes mellitus y las comarcas más meridionales de Cataluña - Monclús Benet, J.F. (Aten Primaria, 2001)
OBJECTIVES: To find the prevalence of diabetes mellitus (DM) and disturbed basal glucaemia in the population over 24 years old and the relationship of this to factors of risk of becoming diabetic. DESIGN: Descriptive, cross-sectional population study. SETTING: Community, county (Baix Ebre - Montsià - Terra Alta) and primary care (9 health districts) context. PATIENTS: Inhabitants of the three most southerly counties of Catalonia over 24 years old (106551 out of 132938). INTERVENTIONS: We randomised from the data base of the computer service of the Catalan Institute of Health (100% coverage), for an estimated prevalence of 15%, losses of 20%, 95% CI and ± 5% accuracy, a sample of 245 people (we studied 198). We informed each doctor of his/her patients in the study. If the patient was diabetic, his/her doctor filled out a questionnaire; if not, the doctor also requested from the laboratory two glucaemia analyses taken after fasting. MEASUREMENTS AND MAIN RESULTS: Using the diagnostic criteria and screening methods of the ADA-1997, we obtained the following results: 1. 14.1% prevalence of DM (1.5% new diagnoses); 4% prevalence of disturbed basal glucaemia. 2. Likelihood of diabetes: age > 45 (4.7 times greater); triglyceridaemia > 250 mg/dl (4.5 times greater); BMI > 27 (2.9 times). CONCLUSIONS: High prevalence of DM, with high proportion known through primary care. We know the prevalence of disturbed basal glucaemia. DM-related risk factors in our population were: age > 45, BMI > 27 and hyper-triglyceridaemia. Our primary care focus can better manage the resources dedicated to DM.